Evaluation of Digitalization Implementation in BMT: Impact on Sharia Financial Inclusion and Member Trust - Rifaatul Indana; M Qoshid Al Hadi (Journal of Islamic Economy and Community Engagement, 2026)
This study aims to analyze the influence of digitalization on efficiency, financial inclusion, and trust among members of Baitul Maal wat Tamwil (BMT) in Yogyakarta, representing Islamic microfinance institutions undergoing digital transformation. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data obtained from 207 active BMT members. The research instrument was developed based on four main constructs and measured using a five-point Likert scale. The results reveal that digitalization has a significant positive effect on operational efficiency, the expansion of Islamic financial inclusion, and the enhancement of members' trust. Furthermore, both efficiency and financial inclusion contribute positively to building trust among BMT members. These findings confirm that the adoption of digital technology not only improves operational performance but also strengthens members' loyalty and confidence in the professionalism and Sharia compliance of the institution. This research provides empirical evidence that enriches the literature on digital transformation in Islamic microfinance, while offering strategic recommendations for BMT managers and regulators to develop a digital ecosystem that is inclusive, efficient, and grounded in Islamic ethical values to ensure the sustainability of Islamic microfinance institutions in the digital economy era.